Executive Cash Compensation and Corporate Performance During Different Economic Cycles* - MATOLCSY, ZOLTAN P. (Contemporary Accounting Research, 2000)
Current practice of management cash compensation is based on financial targets. The financial targets for a year may be above, equal to, or below the previous year's publicly available performance measures based in part on the prevailing economic conditions. Accordingly, during economic downturn, a flat relation between changes in management cash compensation and simple changes in corporate performance, like annual profits or return on equity, is predicted, while during economic growth, a positive relation is predicted between changes of management cash compensation and corporate performance measures. The evidence in this study is based on the period 1987‐95. Pooled, cross‐sectional results are consistent with the propositions of no relation between changes in management cash compensation and changes in measures of corporate performance during periods of economic downturn and significant positive relation during economic growth. Further sensitivity analysis of these results with respect to market‐based performance measures, size, and industry classifications confirm the main results.